Implementasi Pengembangan Karakter Cinta Damai dan Tanggung Jawab melalui Ekstrakurikuler Tapak Suci - Ayu Anggraeni, Dyah (2016)
This study aimed to describe the forms of character development of peace and responsibility in extracurricular tread the sacred, to describe the obstacles faced by teachers in developing the character of peace and responsibility in extracurricular tread the sacred, and to describe solutions to overcome obstacles in developing the character of love peace and responsibility in extracurricular holy site in SMP Muhammadiyah 1 Surakarta in the academic year 2014/2015. This research is a qualitative descriptive study. These research subjects are the principal areas of curriculum, teacher holy footprint, graders SMP Muhammadiyah 1 Surakarta academic year 2014/2015. The object of this study is to develop a peace-loving character and responsibility in extracurricular sacred site, including constraints and handling solutions. Data collection techniques in this study include interview, observation and documentation. Test the validity of research data using a triangulation of data sources and data collection techniques The results of this study can be concluded that: 1) The forms of implementation of peace-loving character development and responsibility in extracurricular holy site in SMP Muhammadiyah 1 Surakarta academic year 2014/2015, namely: a) The development of peace-loving character and responsibility given teachers through extracurricular footprint sacred to practice martial arts with the aim to provide assistance to the needy as a necessity that is done in a common life, b) Master always provides basic training martial arts that can be used as appropriate, c) When practicing always echoes Takbir together in order to maintain the unity of the same other, d) the obligation that must be carried imbued with martial arts, e) Exercise tread the holy offset by the development of polite santu added familiarity of communication that exists in a common life, f) the confidence of the students will arise when teachers trained to provide resistance one on one , 2) Constraints faced, namely: a) Teachers have constraints of students lacking any confidence to practice, b) Students are considered less able to help because they are still small, c) Students often pay less attention to those described by teachers, d) Confidence others still less because they assume are still children who can not help are fully, e) Familiarity with other students less intact, f) less daring students involved in real life. 3) The solutions to overcome the obstacles, namely: a) The teacher gives leeway time during training to enable students to establish familiarity with each other, b) Master emphasized to train hard as a necessity that is useful to a life together, c) training one on one in an effort increase self-confidence in students, d) the teacher gives examples to protect yourself and others, e) Teachers do not forget to slip the sacred footprint examples of obligations that should be done every one to live with.